A Companion to Creative Writing 2013
DOI: 10.1002/9781118325759.ch21
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Creative Writing

Abstract: 21Approximately 3 billion books are sold each year in the United States, and more than a quarter of the population reports reading more than 15 books per year (Ipsos 1). The work of creative writers -including novelists, poets, playwrights, screenwriters, and sitcom writers -has a significant impact on our lives. Not surprisingly, creative writers elicit much curiosity from their audience. Freud had already noted that "We laymen have always been intensely curious to know . . . from what source that strange bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…The flourishing of creative writing workshop in native English speaking universities provides further confirmation that it is effective in cultivating students' writing ability. This has been proved by many scholars of language teaching (Howe, 2016;Forgeard, M., Kaufman, S. B., & Kaufman, J. C., 2009;Krom, C. L., & Williams, S. V., 2011;Nick, E., 2005;Moxley, 1989). For instance, according to Nick (2005), English creative writing workshop is effective in enhancing English writing ability by giving students both a more thorough understanding of literature and alternative but equally valid ways of expressing their feelings; and Moxley (1989) also confirmed that creative writing is very effective in training students' English writing ability.…”
Section: Theoretical Basismentioning
confidence: 87%
“…The flourishing of creative writing workshop in native English speaking universities provides further confirmation that it is effective in cultivating students' writing ability. This has been proved by many scholars of language teaching (Howe, 2016;Forgeard, M., Kaufman, S. B., & Kaufman, J. C., 2009;Krom, C. L., & Williams, S. V., 2011;Nick, E., 2005;Moxley, 1989). For instance, according to Nick (2005), English creative writing workshop is effective in enhancing English writing ability by giving students both a more thorough understanding of literature and alternative but equally valid ways of expressing their feelings; and Moxley (1989) also confirmed that creative writing is very effective in training students' English writing ability.…”
Section: Theoretical Basismentioning
confidence: 87%
“…There is no precise definition of what creative writing is, as many interpretations have been given to the concept of creativity (Kotopoulos, 2012). In an attempt, therefore, to clarify the term, we could say that it is the understanding, exploration and recording of experience (Marshall, 1974), the re-creation of emotional experiences (Sharples, 1996), the spontaneous expression of thoughts and feelings (Gerard, 1996), the enhancement of imagination (Hooker, 1997), the organization and revision of ideas (Harmer, 2004), a discipline involving knowledge and techniques (Dawson, 2005), the original composition (Evernett, 2005), expressive art (O'Rourke, 2005), poetry, prose, drama (HMIE, 2006), a tool of various types of therapy (Morley, 2007), imaginative interpretation of the world (Bennett et al, 2008), intuition and personal memories (Maley, 2009), active engagement with reading and writing (Freiman, 2009), creating imaginative narratives (Nettle, 2009), developing thinking skills (Chen & Zhou, 2010), originality (Temizkan, 2011), the free expression of opinions and feelings (Oral, 2012), a field of research in psychology (Forgeard, Kaufman & Kaufman, 2013), the connection of new information with previous information (Demir, 2013), a kind of catalyst in discussions about cultural differences (Harper, 2014), self-expression in an imaginative way (Ghani & Din, 2017), and finally, creative writing is limitless, as it has the potential to accept all writers, asking them to be completely original (MacVean, 2016), while also being linked to all three aspects of literacy: the functional, the critical and the creative (Kiosses, 2019). In education, the benefits of creative writing are manifold: a) It helps to develop language at all levels, including grammar, vocabulary and phonology.…”
Section: Creative Writingmentioning
confidence: 99%
“…Creativity is a multifaceted psychological phenomenon that has gained increasing attention in the field of psychology (Forgeard et al, 2013). While creativity has historically received less attention in psychology, there is a growing interest in understanding the psychological factors that influence and motivate creativity (Grant & Berry, 2011).…”
Section: Creativity and The Psychologymentioning
confidence: 99%